P-205 How to provide a volunteer befriending service: recommendations from a wait-list controlled trial. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Walshe, Catherine; Dodd, Steven; Algorta, Guillermo Perez; Hill, Matthew; Ockenden, Nick; Payne, Sheila; Preston, Nancy
Abstract : Background: Many innovations in palliative care are commenced without robust research to understand either their impact, nor explore the processes, barriers and facilitators to effective implementation of the service. Within the hospice sector there are an increasing number of volunteer befriending or good neighbour services, and evidence is needed on how best to provide these to improve outcomes. Aim: To make evidence based recommendations on how to deliver effective volunteer befriending services at the end of life. Methods: A wait-list controlled trial (ELSA) (with eight nested qualitative case studies) testing volunteer delivered befriending services across 11 hospice, charity and NHS sites. Participants were estimated to be in their last year of life, randomly allocated to receive the befriending intervention immediately or after a four week wait. Data collection at baseline, four, eight weeks assessed patient's quality of life, loneliness and social support. The case studies included in-depth qualitative interviews with staff, volunteers, patients and family carers. ISRCTN 12929812 . Results: 195 people entered the trial, and interviews were conducted across eight case study sites with volunteers (n = 23), staff (n = 31), patients (n = 24) and family carers (n = 3). Key issues include strategies for maximising impact (e.g. frequency and length of visits, type of support provided, targeting patients), the precise nature of the volunteer role (social or practical, in home or getting out and about), effective running of the service (e.g. how to match volunteer and patient, supporting volunteers), and managing the different nature of a volunteer delivered service(e.g. volunteer training, negotiating boundary issues). Conclusions: We will provide evidence based recommendations on how to run a high quality volunteer befriending or good neighbour service in an effective, safe and well managed way which is likely to maximise impact. Funded by the UK Cabinet Office. See also oral presentation on volunteer befriending services on page (A6).